2018
DOI: 10.1007/s00216-018-0889-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metabolic pathways of different α-N-heterocyclic thiosemicarbazones

Abstract: Clinical failure of novel drugs is often related to their rapid metabolism and excretion. This highlights the importance of elucidation of their pharmacokinetic profile already at the preclinical stage of drug development. Triapine, the most prominent representative of α-N-heterocyclic thiosemicarbazones, was investigated in more than 30 clinical phase I/II trials, but the results against solid tumors were disappointing. Recent investigations from our group suggested that this is, at least partially, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Aside from toxicity due to copper or iron chelation, it was thought that part of the toxicity of the TSCs is related to the release of H 2 S during metabolism. 24 In fact, structure−activity relationship (SAR) studies in which the thiocarbamoyl structure was replaced by a 2-pyridinyl moiety showed a drastic reduction in toxicity and retention of biological activity. 25 The general design principle behind this class of chelators is similar in that the thiocarbamoyl moiety is replaced by a benzothiazole or benzoxazolyl.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Aside from toxicity due to copper or iron chelation, it was thought that part of the toxicity of the TSCs is related to the release of H 2 S during metabolism. 24 In fact, structure−activity relationship (SAR) studies in which the thiocarbamoyl structure was replaced by a 2-pyridinyl moiety showed a drastic reduction in toxicity and retention of biological activity. 25 The general design principle behind this class of chelators is similar in that the thiocarbamoyl moiety is replaced by a benzothiazole or benzoxazolyl.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…No anodic processes were detected for H 2 L1-H 2 L3 in the available potential window. 3 Redox processes detected only upon reversing the potential scan direction at a low cathodic potential limit, or after the formation of wave I red at sufficiently low scan rates. Wave L red was also detected in the derived Cu(II) complexes 1-3 at the same potential value (Figures 4 and S2), therefore suggesting that the redox process was located far off from the influence of the metal center.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Great interest has been reserved in the last decades to the chemistry of thiosemicarbazones (TSC) of the type X-C(Z)=N-NH-C(=S)Y, where different combinations of X, Y and Z moieties have been introduced in the framework. This allows for the modulation of the lipophilic properties, chelating abilities and steric hindrance, also by the presence of additional functional groups, in order to attain an overall synergistic effect for their desired biological activity as such or that of their metal complexes [1][2][3][4][5][6][7][8][9][10][11][12]. A wide range of medicinal effects of thiosemicarbazones are well known (Chart 1): 1-methylisatin 3-TSC (Marboran, no longer produced as a drug) as being antiviral [13], 4-acetylaminobenzaldehyde-TSC (amithiazone, [14,15]) for the treatment of tuberculosis, 4-isopropylbenzaldehyde-TSC (cutisone [16]), 1,4-benzoquinone-amidinohydrazone-TSC (ambazone, [17]), di-2-pyridylketone-4,4′-dimethyl-3-TSC [18] and 3-amino pyridine-2-carboxaldehyde-TSC (Triapine, it has undergone Phase I and Phase II clinical trials, [19,20]) as potential antitumor drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue that manifested was a short-lived patient response, suggesting patients develop resistance [ 24 , 30 ]. Triapine is rapidly metabolised and its metabolite is inactive, rendering it ineffective against solid tumours [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%